1992
DOI: 10.1021/j100186a068
|View full text |Cite
|
Sign up to set email alerts
|

Solvent diffusion in the presence of semipenetrable, rodlike polymers

Abstract: The translational self-diffusion coefficient of a solvent (D) in two rodlike polymer/solvent systems, poly(benzy1 glutamate) in dimethylformamide (PBLG/DMF) and poly(n-butyl isocyanate) in benzene (PBIC/benzene), was measured by pulsed gradient spin echo nuclear magnetic resonance. D decreases monotonically with polymer concentration at all temperatures and polymer rod lengths studied. DMF diffusion was independent of PBLG molecular weight and dropped more than a factor of 5 as 50 vol 7% polymer was approached… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1993
1993
1994
1994

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…Earlier work by Róssler et al at much lower temperatures in PS/toluene solutions indicated a very broad distribution of solvent rotation times. 26 Both of these results are qualitatively consistent with our observation in the PS/THF system.…”
Section: Techniques and Resultssupporting
confidence: 91%
“…Earlier work by Róssler et al at much lower temperatures in PS/toluene solutions indicated a very broad distribution of solvent rotation times. 26 Both of these results are qualitatively consistent with our observation in the PS/THF system.…”
Section: Techniques and Resultssupporting
confidence: 91%